The First Laser Retroreflector on the Lunar Far Side Onboard China’s Chang’e-6 Lander - Yexin Wang; Simone Dell’Agnello; Kaichang Di; Marco Muccino; Hongqian Cao; Luca Porcelli; Xiangjin Deng; Lorenzo Salvatori; Jinsong Ping; Mattia Tibuzzi; Yuqiang Li; Luciana Filomena; et al. (Space: Science & Technology)
The Chang’e-6 (CE-6) lander-ascender combination softly touched down at the designated landing site in the Apollo basin within the South Pole–Aitken (SPA) basin on 2024 June 2. As one of the 4 international payloads onboard CE-6, the INstrument for landing-Roving laser Retroreflector Investigations (INRRI) was installed on the top panel of the lander. Developed by the Italian National Institute for Nuclear Physics–Frascati National Laboratory (INFN-LNF), with support from ASI (Italian Space Agency), this Italian instrument had already been deployed on Mars surface missions: ExoMars (ESA-ASI), InSight (NASA), and Perseverance (NASA). The piggybacking of this instrument came through the collaboration between Italian and Chinese scientists in response to an international Announcement of Opportunity issued by the China National Space Administration in 2018. To optimize its mounting on the CE-6 lander, adaptive design and environmental qualification tests were conducted to meet the requirements of surviving on the far side lunar surface environment. The INRRI retroreflector can be observed using the laser altimeter onboard the Lunar Reconnaissance Orbiter (LRO) and future lunar orbiter missions (e.g., Chang’e-7). The successful landing of CE-6 establishes the first permanent location marker on the Moon’s far side, and it will serve as an absolute control point to support lunar surface positioning and mapping, and orbit determination and navigation of future lunar orbiters with laser ranging instruments.